Cadmium exposure in living organisms: A short review - Zhang, Hao; Reynolds, Mindy (The Science of the total environment, 2019)
Cadmium (Cd) is a toxic heavy metal that accumulates in living systems. Exposure can occur occupationally or environmentally. Workers within the electroplating, battery production, and pigment industries are at the highest risk for exposure and have been reported to have increased levels of Cd in their blood and urine. Environmental exposure can be the result of anthropogenic activities or smoking. Cd has a long half-life and bio accumulates in plants, invertebrates, and vertebrates. The toxic effects following exposure include growth retardation and organ system toxicity, with kidney and liver toxicity most reported with in higher organisms. At the molecular level, Cd leads to the production of reactive oxygen species, DNA damage, and inhibition of DNA repair. This article gives a brief overview of the correlations between exposure to cadmium occupationally and environmentally and levels measured in blood and urine. It also examines the bioaccumulation of cadmium in aquatic invertebrates and vertebrates indicating that accumulation varies not only by location but also within and between various species. [Display omitted] •Exposure to cadmium can occur occupationally of environmentally.•Cadmium exposure can be measured using blood and urine samples.•Cadmium bio accumulates in vertebrate and aquatic invertebrate organisms.•Free cadmium can accumulates aquatic organisms leading to biotransfer into vertebrates.•Cadmium exposure leads to ROS production and DNA damage.